A qualitative exploration of the experiences of community dwelling older adults with sensory impairment/s receiving polypharmacy on their pharmaceutical care journey. (7th August 2019) - Smith, Annetta; Macaden, Leah; Kroll, Thilo; Alhusein, Nour; Taylor, Andrea; Killick, Kirsty; Stoddart, Kathleen; Watson, Margaret
Abstract: Background: Most developed countries have increasing numbers of community dwelling older people with both multi-morbidity and sensory impairment that includes visual, hearing or dual impairment. Older people with sensory impairment are more likely to have chronic health conditions and to be in receipt of polypharmacy (>4 medicines). It is important to understand their experience of pharmaceutical care provision to facilitate a safe, appropriate and person centred approach. Aim: this study explored the pharmaceutical care experiences and perspectives of older people with sensory impairment receiving polypharmacy. Design and setting: exploratory qualitative study with semi-structured telephone or face-to-face interviews with community dwelling older adults with sensory impairment receiving polypharmacy in Scotland in 2016. Methods: in total, 23 interviews were conducted with older people from seven of the 14 Scottish Health Board areas. Subjects: over half the participants ( n = 12) had dual sensory impairment, six had visual impairment and five had hearing impairment. Results: three overarching themes were identified reflecting different stages of participants' pharmaceutical care journey: ordering and collection of prescriptions; medicine storage; and administration. At each stage of their journey, participants identified barriers and facilitators associated with their pharmaceutical care. Conclusions: this is the first comprehensive, in-depth exploration of the pharmaceutical care journey needs of older people with sensory impairment. As the number of community dwelling older people with sensory impairment and polypharmacy increases there is a requirement to identify challenges experienced by this population and offer solutions for safe and effective pharmaceutical care provision.